The Transformation of PAI Learning Based on Deep Learning in Shaping Students' Religious and Critical Character: A Case Study at SMAN 2 Blora - Siti Nur'aini; Srifariati Srifariati; Risdiani Risdiani (Sekolah Tinggi Agama Islam Muhammamdiyah Blora, 2026)
This study aims to explore the transformation of Islamic Religious Education (PAI) learning based on a deep learning approach in shaping students’ religious and critical character at SMAN 2 Blora. Deep learning in this context refers to a student-centered learning approach that emphasizes meaningful understanding, reflective thinking, contextual engagement, and the internalization of values rather than mere memorization. This research employed a qualitative case study design to gain an in-depth understanding of how deep learning principles are implemented in PAI classrooms and how they contribute to character formation. Data were collected through classroom observations, in-depth interviews with PAI teachers and students, and documentation analysis. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the transformation of PAI learning through deep learning strategies such as problem-based learning, reflective discussions, contextual case analysis, and collaborative activities—encourages students to critically examine religious texts and relate them to contemporary social issues. This approach fosters not only a stronger religious commitment, reflected in attitudes of responsibility, honesty, and spiritual awareness, but also enhances students’ critical thinking skills in analyzing moral and societal challenges. Furthermore, the teacher’s role shifts from knowledge transmitter to facilitator and mentor, creating a more dialogical and participatory learning environment. The study concludes that deep learning based PAI instruction significantly contributes to the holistic development of students’ religious and critical character in the secondary school context